Retrospective study on predictive scoring system for amputation in open fracture of tibia type III - Karna, Made Bramantya (International Journal of Research in Medical Sciences, 2017)
Background: Mangled leg remains a challenge in the surgical treatment. Mangled extremity severity score (MESS) is often used as a predictive scoring system. However MESS considered less sensitive because there are still many patients facing amputation legs should be maintained in the end. For that reason, it is necessary to evaluate the counting system has been used. Methods: The study design was a retrospective study using medical records of patients with open fractures of the tibia grade III in emergency room of Dr. Soetomo hospital. From the data on patient medical records, MESI, PSI, HFS, LSI, MESS and NISSSA was calculated. Then the results are assessed by sensitivity, specificity, PPV and NPV. Results: Patients who undergo amputation were 12 people and who successfully maintained limb were 46 people. The sensitivity ranged from 50% (MESI) until 75% (HFS), a specificity ranging from 61% (HFS) until 85% (NISSA). Positive predictive value ranged between 23% (PSI) and 53% (NISSA) and negative predictive value ranged from 81% (PSI) until 91% (NISSA). Conclusions: This study failed to demonstrate the usefulness of the six counting system because it only shows the sensitivity and specificity in distinguishing limb amputation injuries that require immediate and that allows it to be maintained. Some have incorrectly predicted the counting system, where some patients were successfully maintained limb had been predicted for amputees and vice versa.